Improving the efficiency of polymer solar cells via a treatment of methanol : water on the active layers. Issue 24 (7th June 2016) - Guo, Biao; Zhou, Weilong; Wu, Mengchun; Lv, Junjie; Yu, Chengzhuo; Li, Fenghong; Hu, Zhonghan
Abstract : Significant improvement in the power conversion efficiency (PCE) of polymer solar cells (PSCs) has been observed when the active layer was treated with a mixture of methanol and water (M : W). Abstract : Significant improvement in the power conversion efficiency (PCE) of polymer solar cells (PSCs) has been observed when the active layer was treated with a mixture of methanol and water (M : W). For the PSCs based on ITO/PEDOT:PSS/PCDTBT:PC71 BM/Al, the PCE was 6.58% when the surface of the PCDTBT:PC71 BM film was treated with pure methanol. However M : W (6 : 1) treatment on the PCDTBT:PC71 BM film could further improve the PCE to 7.44% which is even higher than the PCE values of the PSCs with LiF (6.00%) or PFN (6.88%) as a cathode interlayer. Similarly in the PSCs based on ITO/PEDOT:PSS/PTB7:PC71 BM/LiF/Al, M : W (6 : 1) treatment on the surface of the PTB7:PC71 BM film can increase the PCE to 8.47% while the PCE values of the PSCs with methanol treatment and without any treatment on the PTB7:PC71 BM film are 8.14% and 7.41%, respectively. Combined contact angle measurements and X-ray photoemission spectroscopy depth profiling demonstrated that the M : W treatments resulted in a more favorable redistribution of the polymer and PC71 BM in the active layer because evaporation of the solvents drove PC71 BM to migrate from the interior of the blend film to the top (air) surface.